Implementasi Marketing Tunnel AIDA pada Metode Pemasaran Digital Search Engine Optimization (SEO) - Aini, Luthfiyah Qurrotul; Samsudin, Acep (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2024)
. This study aims to identify and explain the relationship and application of the AIDA concept to Search Engine Optimization (SEO) optimization on websites and several other digital marketing media. The research method used is descriptive qualitative with data collection using literature study techniques. The application of the AIDA concept can be seen in the opening, body and closing sections of the article.